ALEYRÓDIDOS (HOMOPTERA: ALEYRODIDAE) EN EL CENTRO Y SUR DE TAMAULIPAS, MÉXICO - Myartseva, Svetlana N.; Ruíz Cancino, Enrique; Coronado Blanco, Juana María (Instituto de Ecología, A.C., 2002)
Eleven species and eight genera of Aleyrodidae were determined in central and southern zones of Tamaulipas. Five species are new records for Tamaulipas.